2023
DOI: 10.2166/ws.2023.029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the water quality of the Niger River in Bamako, Mali, based on the Water Quality Index

Abstract: The Niger River, threatened by human activities, is mainly the drinking water source for the population of Bamako city. This study assesses the trend of Niger River pollution in Bamako using the Water Quality Index (WQI). Fourteen parameters, namely Turbidity, Potential of Hydrogen (pH), Electrical Conductivity, Dissolved Oxygen, Total Dissolved Solids, Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), Nitrate, Nitrite, Ammonium, Phosphate, Sulphate, Chloride and Copper, were employed to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Thus, they support multiple index approaches to irrigation water quality assessment (Ezea et al, 2022). This study's results confirm Sangare et al's (2023) recent findings about using the Niger River water for irrigation. Those authors determined the pollution status of the Niger River based on the simple water quality index (WQI).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, they support multiple index approaches to irrigation water quality assessment (Ezea et al, 2022). This study's results confirm Sangare et al's (2023) recent findings about using the Niger River water for irrigation. Those authors determined the pollution status of the Niger River based on the simple water quality index (WQI).…”
Section: Resultssupporting
confidence: 91%
“…The concentration of all parameters, except for NO 3 − , PO 4 3− , and K + , is higher during the high flow (wet season) compared with the low flow (dry season). The high concentration of the parameters in the wet season could be explained by the cumulated effects of rain (runoff) and discharges from households and industrial units in the capital city of Bamako (see Sangare et al, 2023). In the same line, Dutta and Sarma (2018) explained that seasonal variation of the parameters' concentration was due to the high land erosion and direct discharge from stormwater drains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis shows two clear trends during the dry and rainy seasons, which describe the instability of the water quality of the Niger River with a more significant temporal variability during the rainy season than during the dry season. The variation in the parameters during the rainy season is explained by the effect of runoff water discharged into the river, which is most often loaded with domestic and industrial wastewater without appropriate treatment in the city of Bamako [66,67]. The same pattern emerged in other studies that reported that most water quality parameters were slightly higher during the wet season than during the dry season [56,66,70].…”
Section: Spatio-temporal Temporal Distribution Of Water Quality Param...mentioning
confidence: 57%
“…The increasing of Chlorophyll-a from May to November was observed during all the high flow periods (wet season) across Bamako city. This high distribution reveals growth of aquatic plants and is due to anthropogenic sources of nutrients that affect the ecosystem and reduce water quality, which is a threat to human consumption [66,67].…”
Section: Spatio-temporal Temporal Distribution Of Water Quality Param...mentioning
confidence: 99%